TECHNOLOGICAL PECULIARITIES OF MODIFYING PROCESSING OF STEEL - S. V. Korneev; V. A. Rozum; I. A. Trusova; A. P. Bezhok; S. P. Zadrutskij (Литьë и металлургия, 2011)
The analysis of technologies of modifying has shown that maximal efficiency is reached at input of additives by the methods allowing to distribute them in regular intervals to distribute them evenly on volume of metal and to provide the minimum charcoal fumes in atmosphere.